Data from subjects receiving intrathecal laronidase for cervical spinal stenosis due to mucopolysaccharidosis type I - Dickson, P.I.; Kaitila, I.; Harmatz, P.; Mlikotic, A.; Chen, A.H.; Victoroff, A.; Passage, M.B.; Madden, J.; Le, S.Q.; Naylor, D.E. (Data in brief, 2015)
Five subjects with mucopolysaccharidosis type I and symptomatic cervical spinal stenosis received intrathecal laronidase in a 4-month pilot study and/or a 12-month extension study [1]. Clinical descriptions of study subjects, nonserious adverse events, individual data tables, and scoring system methods are provided. There were ten nonserious adverse events that occurred in more than one study subject. Somatosensory evoked potentials were absent in two subjects and normal in two subjects, limiting their utility as an endpoint. There were no significant changes in magnetic resonance imaging of cervical spinal cord or brain, pulmonary function tests, or cerebrospinal fluid opening pressure. These data are presented along with the scoring methods used in evaluation of the study subjects.